The Impact of Human Relationships to Material Acquisition in Construction Projects - Hasim, Sulaiman; Belayutham, Sheila; Che Ibrahim, Che Khairil Izam; Abdul Rahman, Abdul Samad; Hanafi, Abdul Ghafur (International Journal of Integrated Engineering, 2023)
Construction projects have long been plagued with issues of delays, over budget and poor quality. One of the main factors that have been associated with the common issues is material acquisition, with delays in the arrival of material, poor material quality, materials that do not comply with the required specification, unavailability of required construction materials, damaged materials, loss of construction materials sent to site, theft and vandalism. Even though construction material acquisition is an arising problem in the industry, the studies conducted in this area is still scarce. Previous studies have mainly focused on isolated subjects in material acquisition, rather than the entire spectrum on the subject matter. Therefore, this study aims to establish the improvement strategies for construction material acquisition from the human relationships perspective. A quantitative questionnaire was sent to the respondents via email, personally distributed to the contractor’s office, WhatsApp’s application and google form to 1200 active contractor that have been registered with CIDB Malaysia under grade G7. The respondents were limited to purposive sampling criteria which have been determined earlier. Based on the data from 286 questionnaires, findings in this research were structured and analysed using descriptive statistical analysis (mean, standard deviation and frequency) with the aid of SPSS24 software. Finding from the results revealed that the improvement of human relationship was critical to improve construction material acquisition hence, addressing urgent issues including long term relationship such as trust, experience, and responsiveness, clearly understand the client’s needs and objectives, establish strategic partnership with suppliers and long-term resources commitment achieved the highest percentage from respondents. Finally, the study on the impact of human relationships to material acquisition in construction projects can be used as a guidance to enhance the construction material acquisition approach for contractors undertaking projects in Malaysia.